2023
DOI: 10.1186/s13007-023-00981-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of an accurate low cost NDVI imaging system for assessing plant health

Abstract: Background Spectral imaging is a key method for high throughput phenotyping that can be related to a large variety of biological parameters. The Normalised Difference Vegetation Index (NDVI), uses specific wavelengths to compare crop health and performance. Increasing the accessibility of spectral imaging systems through the development of small, low cost, and easy to use platforms will generalise its use for precision agriculture. We describe a method for using a dual camera system connected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 63 publications
(63 reference statements)
0
12
0
Order By: Relevance
“…Numerous studies have explored the utilization of remote sensing with satellites to monitor the health, yield, and growth of bean crops [15,34]. The NDVI, for instance, is commonly employed to assess crop health and vegetative density [2,83,84], while water indices such as NDMI_GAO and NDWI_GAO are more specific for evaluating water availability in plants, as highlighted in several studies [57,58,85].…”
Section: Satellite Data Analysis (Sentinel-2a/msi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have explored the utilization of remote sensing with satellites to monitor the health, yield, and growth of bean crops [15,34]. The NDVI, for instance, is commonly employed to assess crop health and vegetative density [2,83,84], while water indices such as NDMI_GAO and NDWI_GAO are more specific for evaluating water availability in plants, as highlighted in several studies [57,58,85].…”
Section: Satellite Data Analysis (Sentinel-2a/msi)mentioning
confidence: 99%
“…Remote sensing, through electromagnetic radiation-plant-sensor interaction, has a high potential for identifying crop conditions because it allows non-destructive assessment quickly and at a relatively low cost [1][2][3]. This tool can be used to define areas for specific management, manage crop fertilization and irrigation [4], control weeds, and estimate crop productivity [5,6], presenting high practical importance, helping producers manage their production and define the price of agricultural products [7].…”
Section: Introductionmentioning
confidence: 99%
“…The study found that feature selection led to an enhancement in the performance of all machine learning models in forecasting the maturity of dry peas. Narrow spectral bands (NSP), red-edge vegetation indices (ReVIs), and RGB-based vegetation indices (RGBVIs) performed better than other predictors in estimating the maturity of dry peas when using the RF classifier due to their sensitivity to changes in plant health and chlorophyll content [105], which are critical indicators of maturity. In addition, previous research has demonstrated the effectiveness of these predictors in estimating plant maturity in various crops [106][107][108], which further supports their use.…”
Section: Performance Of Uas-derived Predictors For Dry Pea Maturitymentioning
confidence: 99%
“…Based on wheat reflectance data, the percent canopy cover and health could be easily determined and monitored in agricultural fields. Vegetation indices derived from spectral bands such as the Normalized Difference Vegetation Index (NDVI) and Normalized Difference Red-Edge (NDRE) are generally used as proxies for crop condition and structure that include but are not limited to canopy cover and crop health [8][9][10]. The NDVI is a ratio of red (640-670 nm) and near-infrared (850-880 nm) spectral bands [11,12], whereas the NDRE is a ratio of red-edge (670-780 nm) and nearinfrared (850-880 nm) spectral bands [13,14].…”
Section: Introductionmentioning
confidence: 99%